Research on the Design Method of Dialect in Chongqing City Culture Brand - Feng, Zhizhi; Areerungruang, Supachai (Asia Social Issues, 2023)
The Chongqing dialect is a living fossil of local culture and integral to national culture. It carries the context of urban development and has the dual attributes of language culture and intangible cultural heritage. Currently, the Chongqing dialect faces the impact of the official language and globalization. This paper research the design method of the Chongqing dialect in the city brand image. The objective is to build a visual atlas of the Chongqing dialect and explore its application scope through workshops and case studies to provide methods for spreading the Chongqing dialect and shaping the city’s brand image. The mixed research method is used to explore the design practice based on the theoretical results and the existing case studies. The participatory action research method is used in the workshop to try to design characters, voice interaction, materials, and technology intervention to build the dialect visual atlas. It also discusses the application of visual transformation of dialect in public transport, tourist attractions, core business districts, museums, and other places in Chongqing. The results show that the research provides a feasible basis for the promotion of Chongqing’s urban brand image, which is conducive to the development of the Chongqing dialect in the urban brand image, and also provides a reference for the design of dialect as the object.